Diagnostic Value of Optical Coherence Tomography and Electroretinogram in Early Detection of Ethambutol-Induced Optic Neuropathy - M. Dio Syaputra; Syntia Nusanti (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2021)
Background: Ethambutol-induced optic neuropathy (EON) is one of the most compelling adverse effect of tuberculosis treatment. Recovery often occur several months after treatment discontinuation. Unfortunately, some studies noted that nearly half of patients still have permanent visual loss. Early detection before clinical symptoms appear is necessary to prevent this devastating adverse effect. Therefore, this review aims to evaluate the diagnostic value of retinal nerve fiber layer (RNFL) thickness and ganglion cell inner plexiform layer (GCIPL) thickness changes with OCT, pattern and multifocal electroretinogram (ERG) changes during ethambutol treatment as early detection of EON. Methods: A comprehensive search was conducted from electronic databases (PubMed, EBSCO, Google Scholar, and Springerlink) using relevant search terms. Articles from offline resources were also included. Included studies were selected based on predefined inclusion and exclusion criteria. Result: Three studies reported significant thinning of RNFL after ethambutol initiation. Increased RNFL thickness in patients with EON and subclinical EON found in 3 studies. Significant macular GCPIL thinning was noted in 1 study. One study reported shortening of P50 implicit time and reduced N95 wave amplitude in pattern ERG. Conclusion: Macular GCIPL thinning suggested to be the first pathological changes detected on patients with ethambutol treatment. It can be concomitant with thickening of peripapillary RNFL and followed by peripapillary RNFL thinning. Pattern ERG may reveal abnormality due to retinal ganglion cell (RGC) dysfunction before RGC loss.